Rancang Bangun Alat Suction Pump Berbasis Arduino Uno Dilengkapi Dengan Indikator Volume Maksimal Cairan Dalam Tabung - Adi Mandalika, Putu Desta; Gunawan, I Kadek Agus Riki; Suandari, Putu Vierda Lya (Jurnal RESISTOR (Rekayasa Sistem Komputer), 2022)
Suction Pump is a medical device with category of life support, to assist medical personnel to suck patient fluids such as mucus, blood, saliva, pus etcetera. The operasional problem are occurs that the amount of liquid sucked exceed the capacity of the liquid tube, so then the liquid will enter the motor. The motor that is exposed with liquid will be damaged, so it cannot be operated. The researcher is designed a suction pump based on arduino uno equipped with an indicator of the maximum volume of liquid in the tube, with the addition of a pressure sensor MPXV4115VC6U as a reader of the pressure value of the motor, as well as an Infrared sensor as a detector to determine the amount liquid that enter to the tube. LED and infrared photodiode will trigger the relay to stop the motor automatically when volume of the tube is already full. The method used is an observational - experimental study. The pressure test results of the suction pump have three data variant. There are 10, 13 and 15 kPa. The 10 kPa pressure test has an error value of 0.1% then at 13 kPa the error value is 0.1% and 15 kPa has an error value of 0.1%. The experiment are done and repeated ten times, to check whether the suction pump will turn off automatically. All experiments were done successfully.